Bridging the Gap: Pre-Service Science Teachers’ Understanding of Ideal Assessment Versus Real Classroom Practices in Schools - Tiara Widya Hastuti,; Hastuti, Masleha (SEARCH: Science Education Research Journal, 2026)
Alignment between university-based teacher education curricula and school practices is essential to ensure that pre-service teachers develop adequate assessment competencies. This study aims to explore the gap between theoretical assessment concepts learned in higher education and the actual assessment practices implemented by pre-service science teachers during their teaching practicum in secondary schools. A qualitative approach was employed using in-depth interviews with pre-service teachers. Data were collected through semi-structured interviews and analyzed using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing. The findings indicate that pre-service teachers gained meaningful experience in conducting science learning assessments, particularly in designing assessment instruments and implementing classroom evaluation. However, a significant discrepancy exists between the ideal theoretical frameworks acquired at the university and the assessment practices in schools. School-based assessments tend to focus on cognitive evaluation through written tests, while the assessment of students’ skills and attitudes is not optimally implemented. This gap is influenced by curriculum misalignment, limited instructional time, and administrative demands.